The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d1ob02451e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel C-nucleoside analogues bearing an anomeric cyano and a 1,2,3-triazole nucleobase as potential antiviral agents

Abstract: A linear sequence to access to a novel series of C-nucleosides bearing a quaternary carbon at the anomeric position tethered to a 4-substituted 1,2,3-triazole ring is described. Most of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…During the preparation of the present manuscript, Lebreton and co-workers published a study of a very similar approach to the synthesis of compounds like 30a , 30b and 32 . 16 As also observed herein, the authors reported difficulties with the cyanation reaction of a protected 4,5-disubstituted triazole ring embedded in a perbenzyl riboside. In our case, the synthesis of an intermediate such as 27 solves this problem by delivering the corresponding protected intermediates 30a and 30b in a 43% global yield from lactone 19 .…”
supporting
confidence: 70%
See 2 more Smart Citations
“…During the preparation of the present manuscript, Lebreton and co-workers published a study of a very similar approach to the synthesis of compounds like 30a , 30b and 32 . 16 As also observed herein, the authors reported difficulties with the cyanation reaction of a protected 4,5-disubstituted triazole ring embedded in a perbenzyl riboside. In our case, the synthesis of an intermediate such as 27 solves this problem by delivering the corresponding protected intermediates 30a and 30b in a 43% global yield from lactone 19 .…”
supporting
confidence: 70%
“…Similar observations concerning the difficulty in amidating unprotected C1′ quaternized triazolyl-C-ribonucleosides have been recently observed. 16 In the case of 30a and 30b, a mixture of products could be detected after heating overnight at 50 °C. Separation of these products from the mixture proved to be a very difficult task, and only partial purification of a product with a protonated exact mass of 630.2717 Da was possible.…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 98%
See 1 more Smart Citation
“…Remdesivir has a cyan substitution at C1′, which is important for its antiviral activity against SARS-CoV-2 and Ebola virus. [61][62][63] Such 1′-CN-substitution on 1,2,3-triazolyl-Cribonucleosides was studied independently by Lebreton [64] and Miranda/Lubin-Germain [65] (Scheme 16a,b, respectively). Both groups started the synthesis by reacting a corresponding lithium alkylidene with per-O-benzyl-ribonolactone 63.…”
Section: S C H E M E 11mentioning
confidence: 99%
“…1 The nucleoside analogues display great anti-tumor and antiviral activities and have become cornerstones of treatment for cancer and viral infections (Figure 1, Table 1). [2][3][4][5][6][7][8][9][10][11] Numerous bioactive modified nucleosides have been produced as a result of the extended quest for clinically relevant nucleoside derivatives. Recent years have seen a lot of research on the conformational restriction of the ribose or deoxyribose furanose ring in the nucleosides, nucleotides, and oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%